Misdiagnoses of Intracranial Hypotension: A Systematic Literature Review and Case Report - Kaubrytė, Gertrūda; Samaitienė-Aleknienė, Rūta (Acta medica Lituanica, 2026)
Background: Despite the difficulties of diagnosing intracranial hypotension (IH), the literature focusing on specific IH misdiagnoses remains scarce. We report on the case of a pediatric patient with spontaneous intracranial hypotension (SIH) caused by thecal sac dilatation due to Marfan syndrome, who was initially misdiagnosed. Additionally, a systematic literature review was conducted, focusing specifically on misdiagnoses of IH.Materials and Methods: The material search for the literature review was performed across PubMed, Scopus, and Web of Science databases. The inclusion criteria were: published within the last ten years, involved human participants, written in English, and included case reports or series with a clear diagnostic pathway, in which a specified initial misdiagnosis was followed by IH as the final diagnosis. Publications were excluded if they did not meet these criteria. Due to the nature of the case reports, reporting bias and certainty assessment were not formally evaluated. Additionally, a single-patient case report was retrospectively analyzed.Results: A 13-year-old woman presented to the emergency department complaining of a severe postural headache, nausea, sleepiness, generalized weakness, dizziness, and loss of appetite. An asymptomatic venous thrombosis and functional headaches were suspected.  The patient was transferred to a third-level hospital, where a magnetic resonance imaging scan of the whole spine revealed thecal sac dilatation. SIH was diagnosed, and, after 3 weeks of conservative treatment, the patient was discharged from the hospital with full recovery. In the systematic review, 24 studies containing 28 patients were included in the final report. The most frequent initial misdiagnoses were Chiari I malformation (39.29%) and migraine (21.43%). 75% of studies identified SIH as a cause of IH, 16.67% determined it was iatrogenic, 4.17% - traumatic, and 1 case report did not include the cause of IH.Conclusions: While the case report illustrates the difficulties in diagnosing IH, the systematic review distinguishes initial misdiagnoses of this condition, of which the most common are migraine and Chiari I malformation.
Keywords: intracranial hypotension; Marfan syndrome; systematic review; case report; misdiagnosis